Developing a Model for Auditing and Evaluating the Internal Control System of Agencies of the Ministry of Public Health - เสาวรัจ, ธัญชนก (Journal of Health Science of Thailand, 2023)
The purposes of this study were to investigate the problems and obstacles in internal control audit and assessment system, and to assess the efficiency of the utilization of the digital technology in internal control audit and assessment system of agencies of the Ministry of Public Health. The study was conducted in qualitative and quantitative aspects. Interviews were conducted by focusing on the problems and obstacles in internal control audit and assessment. A set of questionnaires was used to collect data in order to assess satisfaction in the efficiency of the utilization of the digital technology in internal control audit and assessment system. The findings of this study were as follow: (A) there were two problems and obstacles in the audit of yearly plan: (1) the finance was high for few audited agencies; and (2) self-assessment: the submission of paper and e-mail assessment results revealed difficulties and complexities of paper collection, data evaluation, scoring, late submission of documents, unable be verified evidence, unsearched for the root causes of the risk, and too many documents to storage that brought about cumbersome and delayed in document search; the Google form submission was just onc time act, and could not re-submit anymore, unable to verify the evidence, unreal scoring, and unable be verified root causes of the risk. (B) The effectiveness of utilizing information technology in internal control audit and assessment on the year 2022 was better than that of the year 2021; and the set goals were achieved, of which the percentage of departments receiving evaluation had increased by 11.68%. The percentage of departments met the evaluation criteria, with the increase of 17.74%. Moreover, it was found that both groups of users were satisfied with the performance at the highest level (Mean = 4.36 and SD = 0.649), in which the user group satisfaction was at a high level (Mean = 4.14 and SD = 0.701), and that of the internal auditors group was at the highest level of performance satisfaction (Mean = 4.58 and SD = 0.596).